1977
DOI: 10.1055/s-0028-1093559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na Pentobarbital Anesthesia on Serum Secretin and Exocrine Pancreatic Secretions

Abstract: The effect of Na pentobarbital anesthesia on serum secretin concentration and exocrine pancreatic secretian was investigated in dogs with chronic gastric and pancreatic fistulas. Na pentobarbital anesthesia was found 1) to reduce basal pancreatic flow rate by 74%, bicarbonate by 70% and protein secretions by 81 % withou t affecting basal immunoreaclive secretin (lRS) concentration; 2) to have no effect on Hel (9.6 mEq/30 min, intraduodenally) mediated IRS release but to reduce by approximately 50% Hel mediate!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This argument, however, can be discarded. We have shown that a given increase in IRS concentration results in a PBS response which is the same regardless of whether it is achieved by infusion of exogenous secretin or through release of endogenous secretin by acidification (Boden et al, 1977). These observations provide direct evidence that HCI induced PBS is secretin mediated and exclude the release of an inhibitor for PBS.…”
Section: Discussionmentioning
confidence: 53%
“…This argument, however, can be discarded. We have shown that a given increase in IRS concentration results in a PBS response which is the same regardless of whether it is achieved by infusion of exogenous secretin or through release of endogenous secretin by acidification (Boden et al, 1977). These observations provide direct evidence that HCI induced PBS is secretin mediated and exclude the release of an inhibitor for PBS.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, although some reports support its existence (12,21), others do not, as values of 14C-erythritol B/P very close to unity have been observed in some studies (22,23). It is possible that distal bile water reabsorption occurs only under specific experimental conditions, e.g., under pentobarbital anesthesia (21,24), and, therefore, until these are defined, the physiological significance of our finding is uncertain. Nevertheless, it is worth mentioning that preliminary studies in our laboratory (25) suggest that the immaturity of this reabsorptive process is associated with the failure of secretin to stimulate bile flow in the first seven days after birth.…”
Section: Discussionmentioning
confidence: 59%
“…This may be related to an inhibitory effect that has been described as a consequence of duodenal perfusion [30]; it may be that this effect is due to the removal of an intraluminal CCK.-releasing peptide [31]. On the other hand, this de crease in protein secretion is a common re sult, even without duodenal perfusion, that has long been described for anesthetized ani mals [32,33].…”
Section: Discussionmentioning
confidence: 99%